The Role of Intra-Operative Duplex Ultrasonography Following Translabyrinthine Approach for Vestibular Schwannoma - Fatima, Nida; Barnard, Zachary R.; Maxwell, Anne K.; Muelleman, Tommy J.; Slattery, William H.; Mehta, Gautam U.; Wagner, Willis; Lekovic, Gregory P. (Frontiers in Surgery, 2022)
Objective: Sigmoid sinus (SS) stenosis is a complication of translabyrinthine approachapproach. Velocity changes in the SS measured by intra-operative doppler ultrasound may help in identifying patients at risk for sinus occlusion. Patients: SS velocity was measured using doppler ultrasound prior to opening dura and again prior to placement of the abdominal fat graft. Intervention: Data collected included: patient age, surgical side, sinus dominance, tumor volume, intra-operative doppler ultrasound measurements, post-operative venous sinus imaging, anticoagulation, and morbidities and mortalities. Main Outcome Measure: SS patency and velocity Results: Eight patients were included in the analysis (22 to 69 years). Four had left-sided and four had right-sided craniotomies. Sigmoid sinuses were either right-side dominant or co-dominant. The mean velocity + standard deviation (SD) prior to dura opening and abdominal fat packing was 23.2+11.3 and 25.5+13.9 cm/s, respectively, p=0.575. Post-operative Magnetic Resonance Venography (MRV) imaging showed four sigmoid sinus occlusions; seven patients showed sigmoid sinus stenosis, and one internal jugular vein occlusion. One patient had post-operative Computed Tomography Venography (CTV) only. Of the four patients with MRV occlusions, CTVs were performed with three showing occlusion and all four-showing stenosis. One patient with internal jugular vein occlusion on MRV received warfarin anticoagulation. There was one cerebrospinal fluid leak requiring ear closure, one small cerebellar infarct, and one with facial nerve palsy (House-Brackman Grade 3) Conclusion: SS velocity changes before and after tumor resection were not predictive of sinus occlusion. We hypothesize that sinus occlusion may be caused by related factors other than thrombosis, such as external compression of the sinus secondary to abdominal fat grafting.